A dança como expressão da educação popular na construção da libertação de corpos femininos - Araújo, Leila Bezerra de (2022)
Thesis work entitled: “Dance as Expression of Popular Education in the Construction of Female Bodies Liberation” searches for constituting interfaces between Popular Education and Dance areas with emphasis on women life stories for identification and oppressions breakdown and the announcement of emancipatory and liberator processes. It has got as central objective to learn with the CorpoMulher Group how the dance expresses itself in Popular Education perspective searching for means for decolonize thoughts, feelings, knowledge and acts in the direction of the construction of female bodies liberation. The study has a qualitative approaching with the methodology of research-action and starts from the contact, participation, cooperation and follow-up of the CorpoMulher Group. This Group is an expansion of the Relaxation and Good Living Vila Saúde Group, extension action linked to the Integral Practices Extension Programme of Health and Nutrition in Basic Care (PINAB) that acts with the Basic Care Unit, in the district of Cristo Redentor, in João Pessoa. The CorpoMulher Group foundation occurred through wider call to the women of the Relaxation and Good Living Group and had the intention to carry out weekly meetings to deepen experiences in Dance, with creative practices oriented by the Popular Education perspective. Eight women, with ages from 54 to 68, with incomplete elementary school (1), complete elementary school (5) and higher education (2), accepted the invitation and contributed for the research elaboration. The information collection and data production occurred through the literature research, documental research, observation – participant and semi structured interview. The narrative analytical stage made emerge three axes of discussion and analysis: Cages opening: dance impressions and oppressions perceived; Strong winds inside: body perceptions; A dance, various flights: understandings and meanings about the construction of female bodies liberation. During the study were addressed issues as coloniality/decoloniality, popular feminism and liberation. The results produced showed that the CorpoMulher Group constituted a feminist prospect made up by the voices, bodies and claims put against the oppressions, mainly by gender relations, and that the construction of knowledge and more organic learnings allowed by the dance aprendizagens favored the change of points of view, the deconstruction of oppressions and the involvement of other ways of flowing through expressing deocolonial practices. Furthermore, indicated that the awareness processes in light of the realities and oppressions experienced enabled by the educative/artistic meetings permeated by Popular Education principles as the dialogue, the active participation, the sharing knowledge and the sharing knowledge construction, meant the path through which was possible to constitute emancipatory and liberating experiences in social, cultural and ideological dimensions of women lives. The thesis put forward here is the Dance, as one of the Popular Education expressions, offers educational strategies that contribute to the female bodies liberation, in social and community works contexts, favoring the women emancipation and autonomy in a radical deocolonial way.